Auditory Authentic Materials in Pronuncing the Words for Kindergarten Students (RETAIN, 2017)
Auditory Authentic Materials in Pronuncing the Words for Kindergarten Students Almira Yasmine English Education, Language and Art Faculty, State University of Surabaya e-mail: yasmine.almira42@gmail.com Abstrak Penelitian ini bertujuan untuk mendiskripsikan penggunaan dari auditory authentic materials untuk taman kanak-kanak sehingga desain penelitiannya adalah kualitatif. Subjek penelitiannya 20 siswa/i taman kanak-kanak di Surabaya Cambridge School. Instrumen penelitian ini menggunakan penangkap suara, catatan, dan wawancara. Selanjutnya, peneliti mengobservasi penggunaan dari auditory authentic materials dan setelah itu menganalisis datanya. Penelitian ini fokus pada linguistic form (berhubungan dengan video) yang menyangkut bagaimana pengucapan baik dan benar dalam bahasa Inggris. Target pelaksanaannya adalah anak usia dini yang mengarah pada bagaimana anak mengembangkan keterampilan belajar yang sama baiknya dengan kemampuan emosi sosial yang menjadi tahap terbaik untuk anak belajar lebih efektif dalam belajar bahasa kedua. Dibuktikan bahwa siswadapat dengan mudah menirukan sama seperti penutur aslinya. Selanjutnya, mereka akan mengingat bagaimana cara menngucapkan kata meski tanpa adanya penggunaan video. Jadi, penggunaan authentic materials sangat penting ketika guru menginginkan siswanya bisa berbicara bahasa Inggris dengan cepat dan baik selancar penutur aslinya yang dimana menambah kesadaran guru. Kata Kunci: bahasa kedua, berbicara, pengucapan, authentic materials, auditory authentic materials. Abstract This study aims to describe the implementation of auditory authentic materials for kindergarten students so that the research design is qualitative research. The subjects of the research are 20 kindergarten’s students in Surabaya Cambridge School. The instruments are recorder, field notes, and interview that be used in this study. Furthermore, the researcher observes the implementation of auditory authentic materials and analyses the field data afterwards. This research focuses on linguistic form (deals with video) that concern on how to pronounce fluently in English. The target of this implementation is early ages because their brain development has a direct on how children develop learning skills as well as social emotion abilities that would be the best stage for children to learn more efficiently in learning second language. This research proved that students can easily imitate as English Native Speaker. Furthermore, they will remember how to pronounce the words even if they do not have the video anymore. Thus, the uses of authentic materials might be crucial if teachers want their student can speak English faster and better as fluently as Native-Like that enhance the teachers’ self-awareness. Keywords: second language, speaking, pronounciation, authetic materials, auditory authentic materials.